2012
DOI: 10.1155/2012/165202
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical Characterization of Briquettes Made from Different Feedstocks

Abstract: Densification of biomass can address handling, transportation, and storage problems and also lend itself to an automated loading and unloading of transport vehicles and storage systems. The purpose of this study is to compare the physicochemical properties of briquettes made from different feedstocks. Feedstocks such as corn stover, switchgrass, prairie cord grass, sawdust, pigeon pea grass, and cotton stalk were densified using a briquetting system. Physical characterization includes particle size distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 39 publications
2
84
0
2
Order By: Relevance
“…The surface area of chrome shavings and buffing dust were finer than fleshing, while the hair was coarser than others. The finer the particle size, the easier the compaction process during densification and the better the quality of the compact [26]. Fine particles give a larger surface area for bonding.…”
Section: Ultimate Analysis Of Pretreated Waste Samplementioning
confidence: 99%
“…The surface area of chrome shavings and buffing dust were finer than fleshing, while the hair was coarser than others. The finer the particle size, the easier the compaction process during densification and the better the quality of the compact [26]. Fine particles give a larger surface area for bonding.…”
Section: Ultimate Analysis Of Pretreated Waste Samplementioning
confidence: 99%
“…In the last four decades, researchers have been focusing on alternate fuel resources to meet the ever increasing energy demand and to avoid dependence on crude oil (Karunanithy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The reserves of non-renewable energy sources such as coal, crude oil and natural gas are not limitless, they gradually get exhausted and their price continually increases. In the last four decades, researchers have been focusing on alternate fuel resources to meet the ever increasing energy demand and to avoid dependence on crude oil (Karunanithy et al 2012). Amongst different sources of renewable energy, biomass residues hold special promise due to their inherent capability to store solar energy and amenability to subsequent conversion to convenient solid, liquid and gaseous fuels.…”
mentioning
confidence: 99%
“…Some studies have focused on the forming mechanism (Adapa et al 2013;Gillespie et al 2013), and others on fuel quality (Kaliyan and Morey 2010;Karunanithy et al 2012). Studies have reported on the energy consumption with this process in a laboratory setting with a single pelleter unit (Ghadernejad and Kianmehr 2012;Hu et al 2013;Song et al 2014).…”
Section: Introductionmentioning
confidence: 99%